Synergy or Trade-Off between Agricultural Growth and Nutrition Women’s Work and Care (The Pakistan Development Review, 2015)
This paper examines the implications of women‘s work in agriculture and children‘s nutritional outcomes in Pakistan. Agricultural growth is an important element of overall economic growth and poverty reduction. It is generally presumed that growth in agriculture will also lead to better nutrition through the higher availability of nutritious foods and increased incomes for the poor. Growth, however, might also imply changes in the amount of time and effort women expend in agricultural work. This may have positive outcomes for nutrition if women have access to their own income, but might also have negative consequences if women‘s agricultural work diminishes their ability to provide nutrition-related care for themselves and their children. The cotton sector which relies very largely on women‘s labour, particularly in harvesting [Siegmann and Shaheen (2008)], can serve as a key vantage point for observing the link between women‘s agricultural work, care and nutrition outcomes in Pakistan. We first set the context for our research by discussing the problem of under nutrition in Pakistan and why agriculture can play a role in improving nutritional outcomes (Section 2). In Section 3, we introduce the concept of care as it exists in the literature the determinants of nutrition review the existing evidence on the relationship between care and women‘s agricultural work. Empirical findings from qualitative research in a cotton-growing region in Pakistan are reported in Section 4. The paper concludes in Section 5 with discussion on how growth in agriculture can be made more inclusiv